Public sector soybean (Glycine max) breeding: Advances in cultivar development in the African tropics. (10th February 2019) - Chigeza, Godfree; Boahen, Steve; Gedil, Melaku; Agoyi, Eric; Mushoriwa, Hapson; Denwar, Nicholas; Gondwe, Therese; Tesfaye, Abush; Kamara, Alpha; Alamu, Oladeji Emmanuel; Chikoye, David
Abstract: Formal public sector soybean breeding in Africa spans over four decades, and it was initiated by the International Institute of Tropical Agricultural (IITA). As the demand of soybean continues to outstrip production, strategic projects such the Tropical Legume (TL) were initiated, in which the main goal was to enhance the productivity of soybean in the farmers' fields in Sub‐Saharan Africa. One of the strategies to enhance the productivity of soybean in the farmers' fields is through developing and deploying improved soybean varieties in the target countries. Through the TL I and TL II projects, a number of varieties were released in the target countries, Kenya, Nigeria, Malawi and Mozambique by employing participatory variety selection (PVS). This review provides highlights of the achievements made by IITA breeding programme and insights of what needs to be done to enhance yield improvement for soybean in Africa using demand‐driven breeding approaches.